2013
DOI: 10.4103/0259-1162.123259
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of recovery profile for propofol and sevoflurane anesthesia in cases of open cholecystectomy

Abstract: Objective:Sevoflurane and propofol are considered to be the agents of choice in surgeries of short duration due to their better recovery profile and few post-operative complications. This study was designed to compare the early recovery profile of sevoflurane and propofol anesthesia in patients undergoing open cholecystectomy.Materials and Methods:A total of 60 patients of either sex with American Society of Anesthesiologists grade 1 and 2 scheduled for elective cholecystectomy were prospectively randomized in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
(28 reference statements)
1
8
0
2
Order By: Relevance
“…20 Similarly Singh SK et al observed that sevoflurane group had better recovery profile with better cognitive function as compared to propofol group, the percentage of patients judged fast-track eligible on arrival in the PACU was significantly higher in the sevoflurane group (75% vs 26%). 2 The results of present study was also concurred with Yao XH et al and Shah A et al who observed that emergence and recovery after maintenance with sevoflurane-N 2 O (group-I) was significantly faster than propofol-N 2 O (group-II).…”
Section: 517supporting
confidence: 91%
See 2 more Smart Citations
“…20 Similarly Singh SK et al observed that sevoflurane group had better recovery profile with better cognitive function as compared to propofol group, the percentage of patients judged fast-track eligible on arrival in the PACU was significantly higher in the sevoflurane group (75% vs 26%). 2 The results of present study was also concurred with Yao XH et al and Shah A et al who observed that emergence and recovery after maintenance with sevoflurane-N 2 O (group-I) was significantly faster than propofol-N 2 O (group-II).…”
Section: 517supporting
confidence: 91%
“…1, 2 The use of appropriate anaesthetic agents that provide fast and smooth induction, allow fast changes in intensity while maintaining anaesthesia and early recovery, and that have no or minimal postoperative side effects are desirable for early hospital discharge. So based on these characteristics, for fast induction and early recovery, newer inhalation agents based on low blood/gas partition coefficients are being used as alternatives to propofol in day care anaesthetic procedures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapid onset of action and short duration of action have made propofol a desirable drug for the induction and maintenance of anesthesia (7). However, the cardiovascu-lar effects of this drug have limited its use, especially in patients with cardiac diseases and hemorrhagic emergency.…”
Section: Discussionmentioning
confidence: 99%
“…11 Penelitian yang membandingkan rumatan anestesi TIVA propofol dengan anestesi sevofluran terhadap operasi kolesistektomi, dengan hasil kejadian mual muntah lebih tinggi pada grup sevofluran, sedangkan pada grup propofol tidak ada kejadian muntah. 12 Penelitian lain yang dilakukan pada operasi nefrolitotomi didapatkan waktu pulih sadar pada grup propofol lebih lama dibanding dengan grup sevofluran, dan angka kejadian mual muntah pascaoperasi pada grup sevofluran lebih besar bila dibanding dengan grup propofol. 13 Penelitian yang dilakukan pada operasi payudara menunjukkan angka kejadian mual muntah pascaoperasi lebih besar pada kelompok sevofluran sebesar 50% dibanding dengan kelompok TIVA propofol 14%, dengan total biaya yang dihasilkan lebih rendah pada kelompok TIVA propofol.…”
Section: Pendahuluanunclassified